Design of a Ukrainian patriotic stamp to identify the state in the context of globalisation - Radomska , Violetta; Ponkalo, Solomiia; Makar, Mariia (Art and Design, 2025)
In the period of search for state identification, the visual culture of postage stamps plays an important social and patriotic component in the representation of the state’s features and historical events in the context of global geopolitics. The main goal of the study was to determine the synchronicity of social constructs, views, and collective perceptions of Ukrainians with the design of the Ukrainian patriotic stamp. The study used general scientific historiographical and special methods. The analysis of the social game Postcrossing showed that postage stamps and epistolary style are undergoing a substantial transformation and popularity within society and beyond, which contradicts the interpretation of the “archaic nature of postage stamps”. It is established that public demand has had a qualitative impact on the dynamic development of stamp issuance in Ukraine. The announcement of competitions to select the optimal and relevant design of a postmark has confirmed the fairly stable positioning of this segment of graphic products as a tool of state-building visual communication. The dynamics of interest and relevance of the postage stamp design are reflected in the implementation of a number of interesting and highly artistic pieces, including the diploma works of students of the Department of Design and Architecture Fundamentals of Lviv Polytechnic National University. The design projects demonstrated that in this type of visual culture, it is important to consider three main components: function, with its specific standards and requirements, theme, and the search for an appropriate and clearly defined figurative and stylistic language. If these segments are accounted for in the design of postage stamps, they will not only serve as a state mark but also contribute to the formation of a holistic identity of Ukraine adapted to the global space.